Leymus chinensis Adapts to Degraded Soil Environments by Changing Metabolic Pathways and Root Exudate Components - Lin, Yulong; Zhang, Pan; Wu, Qingying; Zhang, Ying; Wei, Qianhao; Sun, Yihang; Wu, Yuchen; Sun, Shixuan; Cui, Guowen (Frontiers in Plant Science, 2022)
Phytoremediation is a promising remediation strategy for degraded soil restoration. Root exudates are the main carrier substances for information communication and energy transfer between plant roots and soil, which play nonnegligible roles in the restoration process. This work investigated the adaptation of Leymus chinensis (L. chinensis) root exudates to different degraded levels of soil and the mechanism of rhizosphere restoration in a 3-year degraded soil field study. We found that the soil quality at each degradation level significantly increased, with the SOM content slightly increasing by 1.82%, moderately increasing by 3.27%, and severely increasing by 3.59%, and there were significant increases in the contents of available nutrients such as AP, AN, and NN. The physiological activities indicated that root tissue cells also mobilize oxidative stress to respond to the soil environment pressure. A total of 473 main components were obtained from root exudates by gas chromatography–time of flight mass spectrometry (GC-TOFMS), including acids, alcohols, carbohydrates, and other major primary metabolites. OPLS-DA revealed that soil degradation exerted an important influence on the metabolic characteristics of root exudates, and the numbers of both up- and downregulated metabolic characteristic peaks increased with the increase in the degree of degradation. Forty-three metabolites underwent clear changes, including some defence-related metabolites and osmotic adjustment substances that were significantly changed. These changes mainly mobilized a series of lipid metabolism pathways to maintain the fluidity of membrane function and help plants adapt to unfavourable soil environmental conditions. The PPP energy metabolism pathway was mobilized in response to slight degradation, and TCA energy pathways responded to the environmental pressure of severe soil degradation.